Colonization Potential to Reconstitute a Microbe Community in Pseudo Germ-Free Mice After Fecal Microbe Transplant From Equol Producer - Liang, Wenou; Zhao, Lichao; Zhang, Jingfeng; Fang, Xiang; Zhong, Qingping; Liao, Zhenlin; Wang, Jie; Guo, Yingyu; Liang, Huijun; Wang, Li (Frontiers in Microbiology, 2020)
Human intestinal microbiota plays a crucial role in the conversion of isoflavones into equol. Usually, human microbiota-associated (HMA) animal models are used, since it is difficult to establish the mechanism and causal relationship between equol and microbiota in human studies. Currently, several groups have successfully established HMA animal models that produce equol through germ-free mice or rats; however, the HMA model of producing equol through pseudo germ-free mice has not been established. The objective of this study is to establish an HMA mice model for equol production through pseudo germ-free mice, mimicking the gut microbiota of an adult human equol producer. First, a higher female equol producer was screened as a donor from fifteen volunteers. Then, mice were exposed to vancomycin, neomycin sulfate, metronidazole, and ampicillin for three weeks to obtain pseudo germ-free mice. Finally, pseudo germ-free mice were inoculated with fecal microbiota of the equol producer for three weeks to establish HMA mice of producing equol. The results showed that (i) the ability to produce equol was partially transferred from the donor to the HMA mice. (ii) most of the original intestinal microbiota of mice were eliminated after broad-spectrum antibiotic administration. (iii) the taxonomy data from HMA mice revealed similar taxa to the donor sample, and the species richness returned to the level close to the donor. (iv) the the family Coriobacteriaceae and genera Collinsella were successfully transferred from the donor to HMA mice. In conclusion, the HMA mice model for equol production, based on pseudo germ-free mice, can replace the model established by germ-free mice. The model also provides a basis for studying microbiota during the conversion from isoflavones into equol.